An Exploration into Teachers’ Technological Mathematics Knowledge: Changling Xiwang Elementary School as A Case Study - Shiwei Tan; Wenrong Jiang (Journal on Education, 2021)
The role of teachers in educational institutions in this era must at least know the duties of teachers as professional educators, namely educating, teaching, guiding, directing, training, assessing, and evaluating students in early childhood education. The main purpose of this study is to find out how the teacher's ability to explore technological mathematical knowledge is in teaching mathematics in the classroom. The research paradigm adopted in this study is qualitative research. The main sample in this study were 24 teachers who teach at Changling Xiwang Elementary School. This research was carried out from March to May of the 2020/2021 academic year. The results showed that the teacher's perception of technological abilities in teaching technology-based mathematics, the ability of mathematics teachers to teach mathematics, and the ability of technology-assisted mathematics teachers to teach mathematics in class were categorized as good. These results indicate that most of the teacher's abilities are classified as good about using technology in teaching mathematics. The research suggests furthering researchers to be able to develop technology-based learning media, especially in the field of mathematics in teaching mathematics material in the classroom. Teachers in this century are advised to keep up with the times that are filled with facilities based on information and communication technology (ICT).